2012
DOI: 10.1017/s1047951112001667
|View full text |Cite
|
Sign up to set email alerts
|

A sibling-controlled, prospective study of outcomes at home and school in children with severe congenital heart disease

Abstract: The present study is strengthened by its longitudinal design, use of teacher informants, and sibling control group. The patterns of problems and limitations discerned, and differential determinants thereof, have clear implications for interventions. We consider these in the light of our previously reported intervention trial with this sample and current outcomes at the 7-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 20 publications
1
36
0
3
Order By: Relevance
“…Although processing speed is understudied in this population, it appears that vulnerabilties in this domain could underlie poor performance in some tasks of executive function as suggested in a previous study (Calderon et al, 2014). Findings regarding attention problems expand upon previous studies by utilizing both patient- and parent-reported symptoms as well as using clinically relevant measures (Calderon et al, 2010; McCusker, Armstrong, Mullen, Doherty, & Casey, 2013). Verbal IQ appears to be unaffected in this sample, which is also consistent with previous studies of children with CHD (Karsdorp et al, 2007), although some studies have found deficits in higher-order language skills, such as use of complex language in social communication (Bellinger et al, 2003).…”
Section: Discussionsupporting
confidence: 61%
“…Although processing speed is understudied in this population, it appears that vulnerabilties in this domain could underlie poor performance in some tasks of executive function as suggested in a previous study (Calderon et al, 2014). Findings regarding attention problems expand upon previous studies by utilizing both patient- and parent-reported symptoms as well as using clinically relevant measures (Calderon et al, 2010; McCusker, Armstrong, Mullen, Doherty, & Casey, 2013). Verbal IQ appears to be unaffected in this sample, which is also consistent with previous studies of children with CHD (Karsdorp et al, 2007), although some studies have found deficits in higher-order language skills, such as use of complex language in social communication (Bellinger et al, 2003).…”
Section: Discussionsupporting
confidence: 61%
“…Given the high frequency of ND abnormalities in this population [18, 130, 131], all D-TGA patients should have a ND evaluation, ideally in early childhood, in keeping with the recent recommendations of the American Heart Association and American Academy of Pediatrics’ Scientific Statement [132]. There is emerging evidence that therapies directed toward improving maternal well-being as well as early therapies for the infant may improve long-term outcomes [133135]. …”
Section: Central Nervous System and Nd Outcomesmentioning
confidence: 99%
“…Children with critical CHD (i.e., CHD that requires cardiac surgery in the neonatal period) are at an increased risk for long‐term behavioural, social and emotional difficulties (McCusker, Armstrong, Mullen, Doherty, & Casey, ; Shillingford et al., ). Data suggest that this risk is partially attributable to parental mental health, which has been shown to be a stronger predictor of long‐term behavioural problems in CHD children than disease‐specific and surgical factors (e.g., time spent on cardiopulmonary bypass, cyanotic vs. acyanotic defect; McCusker et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Children with critical CHD (i.e., CHD that requires cardiac surgery in the neonatal period) are at an increased risk for long‐term behavioural, social and emotional difficulties (McCusker, Armstrong, Mullen, Doherty, & Casey, ; Shillingford et al., ). Data suggest that this risk is partially attributable to parental mental health, which has been shown to be a stronger predictor of long‐term behavioural problems in CHD children than disease‐specific and surgical factors (e.g., time spent on cardiopulmonary bypass, cyanotic vs. acyanotic defect; McCusker et al., ). It is well established that compromised parental mental health can lead to long‐term cognitive and behavioural problems in healthy children (Lyons‐Ruth, Wolfe, & Lyubchik, ; McPeak, Sandrock, Spector, & Pattishall, ; Mirhosseini et al., ; Tronick & Reck, ), and several theories have been articulated over the last 40 years to explain how parenting stress, parental mental health and child development are related (e.g., Abidin, ; McCubbin & Patternson, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation